A clinical audit of newly established intensive care unit in the Far Western Region of Nepal - Paneru, Hem Raj; Sharma, Padam Prakash Dev; Kamar, Sher Bahadur; Acharya, Subhash Prasad; Marhatta, Moda Nath (Journal of Chitwan Medical College, 2017)
Abstract available on the PDF.